STUDI TENTANG ANGKA KUMAN UDARA DI RUANG OPERASI RSUD TUGUREJO SEMARANG - Angga Dwi Sulistya; Suhartono Suhartono; Dharminto Dharminto (Jurnal Kesehatan Masyarakat (Undip), 2017)
The operating room is one of the facilities at the hospital and included as the facility has many requirements. This facility is used for patients who need action operation, especially for major surgery. The purpose of this research is to know the description of airborne germ in the operating room the  Semarang Tugurejo Local General Hospital. Research is a descriptive cross-sectional study design uses a cross by using purposive sampling method. The population in this research is the eight-room operations at the Semarang Tugurejo Local General Hospital with as many as 12 samples of two operating room surgery operating room 7 and 8. Analysis of the data used is the univariate form tables mean, SD, median, maximum value, minimum value and an accompanying narrative. The result of research on operating room 7 before sterilization the mean temperatures was 22,50OC, the mean humidity was 43%, the mean illumination was 437 lux, the mean airborne germ was 54,67 CFU/m3. In the operating room 7 after sterilization the mean temperature was 22,13oC, the mean humidity was 45,67%, the mean illumination was 436,33 lux, the mean airborne germ was 24 CFU/m3. In the operating room 8 before sterilization the mean temperature was 22,67oC, the mean humidity was 49,33%, the mean illumination is 472 lux, the mean airborne germ is 32,67 CFU/m3. Temperature after sterilization in operating room 8 is 22,2oC, Humidity after sterilization in operating room 8 is 47%, illumination after sterilization in operating room 8 is 480 lux, airborne germ after sterilization in operating room 8 is 32 CFU/m3. The results of the identification of bacteria in the room 7 and 8 operation is the bacterium Bacillus sp., Staphylococcus aureus, Staphylococcus epidermis, Staphylococcus saprohyticus. Conclusion of this research is to air germ number in the operating room Semarang Tugurejo Local General Hospital do not the standards.